La montée du niveau de la mer d'ici 2100 Scénarios et conséquences - Lacroix, Denis (éditions Quae, 2021)
By at least 2100, humanity will have to face the inevitable phenomenon of rising sea levels. This phenomenon will increasingly affect the coastline and coastal areas where many populations and economic activities are concentrated. The vulnerability to submersion of this interface between land and sea is therefore very high, with increased exposure of delta areas, islands and coastal plains at low altitudes. Risk prevention is therefore a major issue for both public policies and private actors. As such, environmental science research must alert and provide tools to anticipate these developments and help provide solutions to reduce and manage the risks associated with this phenomenon. Using prospective analysis methods, and starting from the main IPCC projections, the authors explore the issues and consequences of several sea level rise scenarios by 2100. This approach aims to shed light on the many actors involved in these scenarios by focusing on support for public policies and research priorities. The book is aimed at actors and decision-makers, public and private, involved in the risks of sea level rise in mainland and overseas France, as well as the various media and the general public wishing to learn about the sea level. future of coastal areas.